An Investigation of Financial Management Behaviors of Managers: Example of KOSGEB - Dayı, Faruk; Esmer, Yusuf; Kukus, Bayram Ali (Journal of Business Research - Turk, 2020)
Purpose - The aim of this study is to analyze managers’ financial management behaviors (cash management, credit management, savings-investment and insurance). Financial management behavior, therefore, plays a key role in the success of managers and organizations. Financial management behavior refers to managers' individual and organizational decisions on and practices in financial matters such as cash, loans, savings, investments and insurance.Design/methodology/approach - Study sample consisted of 85 managers of KOSGEB (Small and Medium Enterprises Development Organization, Turkey). Data were collected using survey method. Data were analyzed using SPSS version 22. Frequency, percentage, mean, standard deviation, reliability, factor analysis and ANOVA were used.Findings - Managers’ financial management behaviors differ by experience, income and education level. The higher their experience, income and education level, the higher their insurance sensitivities. Managers have high tendency to credit management and cash management behaviors, moderate tendency to savings-investment behaviors and medium to low tendency to insurance behaviors. This result indicates that managers do not attach enough importance to insurance, in other words, they are not cautious enough about insurance.Discussion - Participants’ financial management behaviors differed by experience, income and education level but not by gender, marital status, age and credit card use. This study is important in the sense that it is one of the fewest studies addressing financial management behavior.
Keywords: İşletme; İktisat; 4. Education; 8. Economic growth